ANALISIS VARIANS ANGGARAN PENDAPATAN DAN BIAYA (STUDI PADA PD. PASAR KOTA KENDARI) - Mustafa, Santiadji; Anugranita, Dwi Ananda (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
AbstractThis study aims to find out the level achievement of the realization of the budget as well as the causes of difference between budget and actual budget in 2014. The data used is the qualitative and quantitative data as well as data source in this research are primary and secondary data. This research is using descriptive analysis by variance analysist  between budgeted and actual revenues and costs. The results of varians analysist showed that Market Local Company Of Kendari City does not reach the budget targets of the budget due to several factors. But in terms of Cost (Expenditure), Market Local company Of Kendari City has been able to improve efficiency and cost effectiveness in operational activities that prove budget realization lower cost than budgeted. Keywords: Budget revenues and costs